STUDY OF PHYSICAL AND MECHANICAL PROPERTIES OF SILK FABRICS AND THEIR ANALYSIS - Sh. X. Muhammadrasulov; M. X. Xoshimova; B. B. Mominov (European Science Publishing, 2023)
The composition, physical-mechanical and hygienic properties of silk fabrics were studied in the research laboratory of the institute and at a manufacturing enterprise. As a result of the study, an analysis of the results of choosing gauze for a blouse showed that the physical, mechanical and hygienic indicators of the selected materials fully meet the requirements of the consumer in all respects.
Keywords: mechanical properties, tensile strain, twisting deformations.